Analisis Investasi Jasa Penyewaan Perancah (Scaffolding) di Kota Palu - Nirmalawati, N.; Dolu, A.; Fadliah, I.; Alit, D.W. (Tadulako University, 2024)
Scaffolding is an auxiliary construction used in multi-storey building construction work, used so that the implementation of work in the field can be easier and faster. As the development of building construction in the city of Palu, the need for the use of scaffolding is increasing. So it is interesting for researchers to find out whether investors in the field of scaffolding rental are still feasible for the coming years to move in this rental sector. The literature study method uses investment feasibility calculations, secondary data is taken from existing data in the field, namely the number of building construction works in Palu city, company financial cash flow data, and uses NPV (Net Present Value), EAV (Equivalent Annual Value), IRR (Internal Rate of Return) , and DPP (Discounted Payback Period). Assume income from the number of rentals and rental prices for the next 20 years. Interest rate of 8% and inflation of 3.85% for a period of 20 years at the PT Lexindo Scaffolding company obtained an NPV value of Rp.2,168,897,376 > 0, an EAV value of Rp.197,646,803 > 0, an IRR value of 33% > 8%, and DPP value of 4.98 years <20 years, for PT. Jaya Scaffolding obtained an NPV value of Rp.6,995,506,453 > 0, an EAV value of Rp.755,554,338 > 0, an IRR value of 30% > 8%, and a DPP value of 5.51 years <20 years. The conclusion states that the investment in scaffolding rental services is still feasible to invest.